Understanding Elementary Students’ Difficulties in Mathematization of Pre-Algebra Problems - Salsabila, Syifa; Jupri, Al; Umayrah, Anggi; Salsabila, Salwa (Universitas Pendidikan Indonesia, 2025)
This study aims to explore the mathematization process of elementary school students in solving pre-algebraic story problems. Adopting a sequential explanatory mixed-method design with a qualitative descriptive case study as the core component, the research focuses on understanding students’ thinking patterns based on their written work and reflections. Participants consisted of 53 Grade V students from three schools in Tasikmalaya, Indonesia. The initial quantitative phase was conducted to identify general patterns of performance and guide case selection for the qualitative phase, while qualitative data were obtained from students’ written outputs, video recordings, unstructured interviews, and field notes. Findings from the initial phase indicated a wide range of abilities, revealing learning gaps that warranted deeper exploration. Qualitative analysis shows that students face difficulties in understanding problem statements, formulating mathematical models, applying operational rules, and re-examining their solutions. The most dominant errors occur in vertical mathematization, particularly in the problem-solving and reflection stages. These findings highlight the urgent need to design classroom practices and learning strategies that explicitly develop students’ mathematization abilities, especially during the transition from arithmetic to algebraic thinking in primary education.